The Effectiveness of Instagram Reels in Improving Students` Speaking Skills at the Sixth Semester of STKIP PGRI Bangkalan - Ela Farida; Siti Maria Ulfa; Ruqoyyah Amilia Andania (Universitas Islam Negeri Palopo, 2026)
Speaking skill is one of the essential aspects of English language learning because students are expected to communicate ideas fluently and confidently. However, many EFL university students still experience difficulties in speaking English, including limited vocabulary, hesitation, low confidence, and pronunciation problems. This study aimed to investigate the improvement of students’ speaking skills after the implementation of Instagram Reels at the sixth semester of STKIP PGRI Bangkalan. Unlike previous studies that mainly focused on students’ perceptions toward Instagram Reels, this study statistically examined students’ speaking improvement using a quantitative pre-experimental design. The study employed a one-group pre-test and post-test design involving 13 EFL university students. The researcher used total sampling because the total population of sixth-semester students consisted of only 13 students. The treatment was conducted in two meetings using Instagram Reels as speaking learning media. The data were collected through speaking tests assessed based on pronunciation, vocabulary, grammar, fluency, and comprehension. The data were analyzed using SPSS through reliability test, normality test, and Paired Sample T-Test. The findings showed that the mean score increased from 9.85 in the pre-test to 16.38 in the post-test. In addition, the significance value (Sig. 2-tailed) was 0.000, indicating a statistically significant improvement in students’ speaking performance after the treatment. The effect size analysis using Cohen’s d showed a very large effect (d = 2.76). The findings suggest that Instagram Reels was associated with positive improvement in students’ speaking skills and can be considered as an alternative learning medium for speaking instruction in EFL classrooms.